基于同伦优化设计的机械零件可靠性优化设计 - 车晓毅; 罗佑新; 徐静蓉; 汪超; 何哲明 (Jixie chuandong)
Generally, action of constraints exists in reliability optimization design of mechanical parts. Usually, general optimum methods are adopted in reliability optimization design, so the local solution is obtained. Aimed at this situation, a new global optimum method, namely, homotopy optimization method （HOM）, was first introduced. The HOM method overcomes the defect of existing homptopy optimization method that wants to take path-tracing, and, the new HOM method can find global optimization solution without necessarily multi-time path-tracing. The result shows the model is practical and effective and its solution is global solution better than the result with general optimum method. As the method is simple, it is worthy to spread in optimum design.